Application of Life Cycle Assessment (LCA) On Green Tea Product (Case Study in the X Company). Issue 1 (January 2021) - Mila, G; Primasari, B; Aziz, R
Abstract: This study analyzes the environmental impact of 1 ton green tea 50 gr canned in x company using the Life Cycle Assessment (LCA) method. A cradle to gate approach was used to scope the study, from plantations to packaging. SimaPro version 9 software is used as a tool for assessing LCA. The evaluation step refers to ISO 14044 of 2006, which determines the objectives and scope, inventory analysis, impact, and interpretation. The method used to assess the environmental impacts is the CML-IA Baseline. The classification results of the dominant and significant impact characterization on the environment are global warming with 475.557, 7 kg CO2 eq. Drying process II, drying process I, PLN electricity, and transportation contribute to the environmental impact. The recommendation for technical improvement based on the sensitivity analysis results is using PLN electricity with renewable energy, namely micro hydro (PLTMH). The combination of wood biomass with other biomass is rice husks, then changing the truck fuel from diesel to fuel that is morm e environmentally friendly Pertamina Dex.